Application of Phosphorus and Determination of Heat Units to Increase Productivity and Isoflavone Content of Several Varieties of Edamame Soybeans - Manullang, Nadya Inri; Melati, Maya; Ghulamahdi, Munif (Journal of Tropical Crop Science, 2025)
Edamame is rich in isoflavones, which offer notable health and beauty benefits. Phosphorus influences the biosynthesis of isoflavones in edamame, making this nutrient an important factor in crop management. Edamame soybeans are harvested at the R6 stage, when pods are fully developed yet still green, a timing that is critical for ensuring optimal quality. Harvest maturity is determined using accumulated heat units, a method that calculates the temperature differences at the planting site to assess crop readiness accurately. This study evaluated the effects of phosphorus fertilization and variety on edamame productivity and isoflavone content. The experiment was conducted at the IPB Experimental Station in Bogor, Indonesia (coordinates: -6.548927° S, 106.734462° E), using a randomized complete block design with three replications. The first factor was phosphorus fertilizer applied at rates of 0, 18, 36, and 54 kg P₂O₅ per hectare. In contrast, the second factor was edamame variety (“Biomax 1”, “Biomax 2”, and “Detam 2” as a check variety for isoflavone content). The results showed no significant interaction between phosphorus fertilization and variety for several growth parameters, including leaf phosphorus content, leaf number, branch number, relative growth rate, and pod weight per plant. However, significant differences among varieties were observed for leaf number and seed weight per plant. Phosphorus fertilization did not significantly affect branch number or pod weight, but it did influence isoflavone content, with different phosphorus doses increasing genistein accumulation in certain varieties. The study also highlighted the impact of temperature on plant growth, as evidenced by significant differences in accumulated crop heat units (CHU) among the varieties: “Biomax 1” required 2029.50–2050.75 °C days, “Biomax 2” required 2070.20–2132.25°C days, and “Detam 2” required 2218.85–2256.05°C days. The highest isoflavone content was recorded in “Biomax 2” with the application of 36 kg P₂O₅ per hectare. Overall, these findings underscore the complex relationship between soil conditions, nutrient availability, and varietal selection in determining edamame yield and quality. This research provides valuable insights for optimizing edamame production and enhancing its nutritional value.